Genistein Induces Alterations of Epigenetic Modulatory Signatures in Human Cervical Cancer Cells - Sundaram, Madhumitha K.; Ansari, Mohammad Zeeshan; Al Mutery, Abdullah; Ashraf, Maryam; Nasab, Reem; Rai, Sheethal; Rais, Naushad; Hussain, Arif (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Introduction: Epidemiological studies indicate that diet rich in fruits and vegetables is associated with decreased cancer risk thereby indicating that dietary polyphenols can be potential chemo-preventive agents. The reversible nature of epigenetic modifications makes them a favorable target for cancer prevention. Polyphenols have been shown to reverse aberrant epigenetic patterns by targeting the regulatory enzymes, DNA methyltransferases (DNMTs) and histone deacetylases (HDACs). In vitro and in silico studies of DNMTs and HDACs were planned to examine genistein’s role as a natural epigenetic modifier in human cervical cancer cells, HeLa. Methods: Expression of the tumour suppressor genes (TSGs) [MGMT, RARβ, p21, E-cadherin, DAPK1] as well the methylation status of their promoters were examined alongwith the activity levels of DNMT and HDAC enzymes after treatment with genistein. Expression of DNMTs and HDACs was also studied. In-silico studies were performed to determine the interaction of genistein with DNMTs and HDACs. Results: Genistein treatment significantly reduced the expression and enzymatic activity of both DNMTs and HDACs in a time-dependent way. Molecular modeling data suggest that genistein can interact with various members of DNMT and HDAC families and support genistein mediated inhibition of their activity. Timedependent exposure of genistein reversed the promoter region methylation of the TSGs and re-established their expression. Conclusions: In this study, we find that genistein is able to reinstate the expression of the TSGs studied by inhibiting the action of DNMTs and HDACs. This shows that genistein could be an important arsenal in the development of epigenetic based cancer therapy.
Keywords: methylation